THE INFLUENCE OF STRONG AND WEAK ACID UPON AGGREGATION AND PHEOPHYTINIZATION OF CHLOROPHYLL A AND B - Lia Kusmita; Leenawaty Limantara (Indonesian Journal of Chemistry, 2009)
Chlorophyll is green pigment that can be found in plant chloroplast. Higher plants usually have two kinds of chlorophylls, chlorophyll a and b. These green pigments are easily degraded by temperature, light intensity, oxygen, acid, and water. Water causes aggregation of chlorophyll, while acid causes pheophytinization of chlorophyll. Aggregation and pheophytinization process of chlorophyll are influenced by solvents. This study was conducted to observe the spectral difference of aggregated chlorophyll in acetone and methanol upon pheophytinization by strong (HCl) and weak acid (CH3COOH), in comparison to the non-aggregated chlorophyll. Observation of spectral pattern was carried out using double beam spectrophotometer CARY 50 at 350-1100 nm. The result shows that pheophytinization of chlorophyll a and b causes hypsochromic shift, particularly at Soret band. There are new peak formations in Qx region, specifically at 506 and 535 nm for pheophytinized-chlorophyll a, and at 371, 435, 526 and 599 nm for pheophytinized-chlorophyll b.